REFORM OF THE CRIMINAL LAW OF ACTIONS ABOUT THE MISUSE OF FIRE WEAPONS IN INDONESIA - Debby Khoirunisa; Indra Yudha Koswara; Taun Taun (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
Since March 8, 1946, the Criminal Code has been used as criminal law in Indonesia, although changes have been made several times in the criminal law code. It is now realized that the Criminal Code is no longer able to accommodate the aspirations of the people who are developing rapidly due to several factors. The development of crimes that occur in society is also evidence that the Criminal Code does not provide legal protection to the community. In analyzing criminal law, one must pay attention to the social norms and standards that have been established and applied by the criminal law. As a result, social norms turn into legal norms. In the context of a democratic society, congruence eventually occurs between various social norms, through social ethics and legal norms. The development of punishment raises the idea or principle of punishment, making the convict a subject rather than an object so that he views the convict as a whole human being. by the Indonesian people, which has received social attention as a result of the search for alternative punishments for other independence crimes.